Conéctate : introductory Spanish / Grant Goodall, Darcy Lear - Goodall, GrantAuthor
Conéctate is a fresh approach in every way. With its focus on the most critical language for communication, its active presentation of vocabulary and grammar, and its inclusion of real-world culture throughout, the program provides a unique framework for the Introductory Spanish course, with two separate but complementary goals in mind: learning to use the language and appreciating the world that it comes from